EFFECT OF POSITIVE EXPIRATORY PRESSURE ON THE VITAL SIGNS IN PATIENTS WITH COPD (Fiep Bulletin - online, 2014)
Evaluate the effects of Positive Expiratory Pressure (EPAP) on vital signs (VS) in patients with COPD. This is a clinical trial single blinded, comprising patients with COPD (n=12) treatment group (WG) with a clinical diagnosis and staging II and III GOLD (Global Initiative for Chronic Obstructive Lung Disease), and healthy subjects (n=13) Control Group (CG) both genders, age between 40 - 70 years. Initially to characterize the groups were evaluated by spirometry lung volumes, the VS as respiratory rate (RR), blood pressure (BP) and heart rate (HR) and oxygen saturation (SpO2) at baseline (Pre-EPAP). It was later applied to EPAP (15 cmH2O) by mask for 25 min, with data logging (VS and SpO2) in the fifteenth and twenty-fifth minute of application of positive pressure. A média de idade dos indivíduos do GC foi de 57,1 ± 7,1 anos e no GT, 57,2 ± 8,3 anos. The values ??obtained in spirometry demonstrated normal lung function in CG (FVC: 87.8 ± 9.6%pred, FEV1 86.8 ± 14.3%pred and FEV1/FVC: 99.0 ± 9.3%pred), and airflow limitation in TG (FVC: 63.7 ± 19.5%pred, FEV1: 44.0 ± 20.0%pred and FEV1/FVC: 66.8 ± 17.4%pred). With the implementation of EPAP increased SpO2 (p
Keywords: .